2014
DOI: 10.1039/c3mb70529c
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the lipidome, inflammatory markers and insulin resistance

Abstract: The objectives of the present study were to (1) examine the effects of the phenotypic factors age, gender and BMI on the lipidomic profile and (2) investigate the relationship between the lipidome, inflammatory markers and insulin resistance. Specific ceramide, phosphatidylcholine and phosphatidylethanolamine lipids were increased in females relative to males and specific lysophosphatidylcholine, lysophosphatidylethanolamine, phosphatidylcholine and phosphatidylethanolamine lipids decreased as BMI increased. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 77 publications
3
66
0
1
Order By: Relevance
“…Our results agree with previous research showing decreased concentrations of different species of lysophosphatidylcholines in obesity or insulin resistance in humans and mice (3,4,10,31) that persist even after weight loss (3). In contrast, increased concentrations of lysophosphatidylcholine species associated with the onset of type 1 diabetes, insulin resistance, and obesity have been described as well (5,6,(32)(33)(34)(35), suggesting that the onset of these alterations might be associated with transient increases of lysophosphatidylcholine.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with previous research showing decreased concentrations of different species of lysophosphatidylcholines in obesity or insulin resistance in humans and mice (3,4,10,31) that persist even after weight loss (3). In contrast, increased concentrations of lysophosphatidylcholine species associated with the onset of type 1 diabetes, insulin resistance, and obesity have been described as well (5,6,(32)(33)(34)(35), suggesting that the onset of these alterations might be associated with transient increases of lysophosphatidylcholine.…”
Section: Discussionsupporting
confidence: 93%
“…). Furthermore, phospholipid reduction is known to have a positive association with insulin resistance . We also observed that most sphingomyelins (SMs) were decreased.…”
Section: Discussionmentioning
confidence: 66%
“…A study investigating associations between BMI, inflammation and insulin resistance demonstrated negative associations between LPC 18: 1 and various adipokines and inflammatory mediators. Low levels of LPC 18: 1 together with increased levels of leptin or CRP were associated with increased HOMA scores [65]. Applied to the results of the current study, altered levels of LPCs hypothetically could affect fetal growth by influencing insulin resistance and insulin secretion.…”
Section: Discussionmentioning
confidence: 73%